Private Military Firms and Responses to Their Accountability Gap - John S. Kemp (Washington University Journal of Law & Policy, 2010)
David Price, a Democratic representative from North Carolina, sponsored the MEJA Expansion and Enforcement Act of 2007 (H.R. 2740), which the House passed on October 4, 2007.12 The bill was intended to update the Military Extraterritorial Jurisdiction Act of 2000 ("MEJA").13 H.R. 2740 proposed adding language to MEJA to clarify that the United States has jurisdiction to hold contractors liable under American criminal law for prohibited conduct committed in regions where the Armed Forces are engaged in contingency operations.The history of private military firms ("PMFs") is discussed in Part I of this Note. Part II explores the controversial nature of PMFs and the consequences of inadequate regulation of the industry. Part III discusses court cases addressing civilian criminal liability abroad. It examines statutes that attempt, rather unsuccessfully, to regulate contractors while they accompany our Armed Forces. An exploration of the narrow reach of the current law in Part IV, however, will highlight the goals of H.R. 2740, explain the necessity of revisiting the bill, and propose changes that will make the law governing private contractors‘ overseas behavior more comprehensive and effective.
Keywords: Private military companies; Criminal liability; Responsibility; Independent contractors; United States. Patriot Act of 2001; United States. Uniform Code of Military Justice; Criminal jurisdiction; Government contractors; Security services industry; Military Extraterritorial Jurisdiction Act of 2000